Properties and uses of butanol - Artois, Arnaud M. (Chemistry research and applications, 2020)
"Properties and Uses of Butanol reviews the different types of butanol along with its characteristics, methods of production and future trends observed in its applications as an alternative energy resource. The main aspects involved in the production of biobutanol are described, including raw materials, the transformation of biomass and the separation of the acetone-butanol-ethanol mixture. The most important areas of opportunity are determined, focusing on the enhancements required by the production process to increase reaction yields in the hydrolysis and fermentation steps. The closing study discusses the oxidation of butanol on Pt single crystal, the possible mechanisms of the butanol oxidation reaction, and the working principles of fuel cells"--